Profile of patients with ocular infections attending the out-patient department of a tertiary care centre in south India - A., Ipe; N., Navaneetha; R., Skariah (International Journal of Research in Medical Sciences, 2017)
Background: Bacterial and viral etiologies are most commonly blamed for ocular infections. Studies have shown that gram positive cocci are responsible for maximum number of infections, followed by anaerobic bacteria and gram negative bacilli. Infections of the ocular adnexa, ocular surface and orbit usually present as conjunctivitis, keratitis, scleritis, orbital cellulitis and periorbital necrotising fascitis. The intra-ocular infections usually occur subsequently to a corneal ulcer, penetrating eye injury or a severe blood stream infection, and presents as iritis, uveitis, chorioretinitis or endophthalmitis. The aim of the study was to find out the clinico-demographic profile of patients who were diagnosed to have ocular infections at a large tertiary care teaching hospital in south India. Methods: A retrospective study was designed to include all patients who came with suspected ocular infections to the out-patient department (OPD) of Pushpagiri Medical College Hospital, Thiruvalla, Kerala, India, from July 2015 to December 2015. Results: More than 50% of the participants reported ocular pain and around 60% has redness of the affected eye. Twenty five percent of the participants had discharge from the eyes and 56.7% reported persistent watering. Around 60% of the patients had irritation of the eye, while only 16.7% said that they feel blurring of vision. The final diagnosis was formed after careful examination by the senior most consultants available at the OPD and relevant investigations. Among the participants, 36.6% had conjunctivitis and 16.6% had corneal ulceration due to an infective cause. Around 13% has corneal abrasion, 11.6% had foreign body, 3% had dry eye and 3% had dacrocystitis. Conclusions: Only around 55% of the patients with suspected eye infections turned out to be actual infections and a vast majority of that was due to conjunctivitis. Though majority of the patients presented with pain, redness, watering and discharge, these symptoms/signs cannot be used to differentiate infective etiology from a non-infective one.